First case of primary intraocular natural killer t-cell lymphoma. Issue 1 (December 2015) - Maruyama, Kazuichi; Kunikata, Hiroshi; Sugita, Sunao; Mochizuki, Manabu; Ichinohasama, Ryo; Nakazawa, Toru
Abstract Background Natural killer cell tumors can be broadly divided by origin into mature-cell and progenitor-cell types. The invasion of nasal-origin natural killer cells into the ophthalmologic field is sometimes observed in patients, but primary ocular natural killer cell tumors are a rare occurrence. Case presentation A 66 year-old woman without any systemic disease presented with blurred vision due to a severe vitreous opacity in the right eye. Flow cytometric analysis of the vitreous fluid suggested a natural killer cell tumor. Moreover, cytologic examination of vitreal and retinal specimens revealed the infiltration of a natural killer cell tumor, while PCR and immunocytochemistry revealed Epstein-Barr virus infection. The results of a gene rearrangement analysis were positive for IGH, while TCR beta chains were all negative. We examined the patient with whole-body magnetic resonance imaging and positron emission tomography, and performed a bone marrow examination. These examinations returned no abnormal results. Conclusion Thorough analysis of vitreal samples is essential when performing vitrectomies for vitreous opacities of unknown cause. Flow cytometric, cytologic, and PCR analysis of vitreal and retinal samples may reveal the presence and cause of severe illness.